DAMPAK REVITALISASI PASAR TRADISIONAL TERMINAL TOBOALI TERHADAP PENDAPATAN PEDAGANG DAN RESPON KONSUMEN DI KABUPATEN BANGKA SELATAN - Fikri Yansyah; Evahelda Evahelda; Yudi Sapta Pranoto (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Biologi Universitas Bangka Belitung, 2021)
This research to describe the income and consumer response in the traditional market revitalization activities of the Toboali terminal. This research was conducted at the traditional market terminal of Toboali village, South Bangka Regency from February 2019 to July 2019. The research method used was a survey method. The sampling method uses simple purposive sampling technique to determine the number of consumer respondents as many as 90 people and traders as many as 30 respondents, as well as the method of processing and analyzing data using descriptive qualitative analysis and the paired t-test. The results showed the existence of revitalization of old buildings and the addition of new buildings. Traders' income before and after market revitalization activities is Rp. 6,339,376.83 per month, as well as consumer responses in the revitalization of traditional market activities in the physical aspects of infrastructure improvement and market building maintenance index figures obtained by 76.44 percent, improvement in market environment cleanliness obtained index numbers by 77.78 percent, an increase in securing and controlling the market obtained an index number of 71.73% and mapping and training of traders obtained an index figure of 81 percent